Kewenangan Pengakuan Hak Pengelolaan Wilayah Laut Kepada Masyarakat Hukum Adat Oleh Pemerintah Daerah - Larubun, Faliuw Samuel; Nendissa, Renny Heronia; Matitaputty, Merlien Irene (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
The state recognizes and respects the unity of customary law communities and their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, which are regulated in law" Article 18(b) paragraph 2 of the 1945 Constitution is the legal basis for recognizing the existence of the community customary law in Indonesia which has rights and authority to be respected and respected. The existence that has been recognized on a clear legal basis means that customary law communities have the authority to manage and manage their own customary territories as they should. The authority that is meant is the authority to manage the land and even the sea which is the ownership right of the indigenous communities themselves. Marine management rights by customary law communities or what is usually called marine ulayat rights are a set of rules or practices for managing marine areas and the resources therein based on customs carried out by coastal communities in villages. Regional Governments are obliged to provide recognition of marine management rights to customary law communities. This is clearly stipulated in Law Number 1 of 2014 in article 20 paragraph (1): The Government and Regional Governments are obliged to facilitate the granting of location permits and management permits to Local Communities and Traditional Communities "But what if the regional government does not grant marine management rights in accordance with the applicable law.